PEMBELAJARAN MELUKIS TEKNIK FINGER PAINTING UNTUK MENINGKATKAN PERKEMBANGAN MOTORIK HALUS DI TK ISLAMIYAH PONTIANAK - Lisdayanti, Resty; Syukri, M.; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the increase in fine motor development in art learning through finger painting techniques in children aged 5-6 years in Southeast Pontianak Islamiyah Kindergarten. The general objective in this study was to describe the learning of painting through finger painting techniques to improve fine motor development in children aged 5-6 years. The research method used was descriptive with a qualitative approach and type of case study research. The data sources of this study included 1 teacher and child group B3 in Islamiyah, which amounted to 16 people as subjects. After data is collected, data is presented to draw conclusions. From the results of the study, it was found that painting through finger painting techniques to improve fine motor development had increased, namely that children could flex their fingers. both with 75% BSH and 25% BSB results. exploring the percentage of MB 37.5%, BSH 43.75% and BSB 18.75%, and children can also do neat activities from the results of the percentage of MB 25%, BSH 68.75% and BSH 6.25%. Increased learning activities in children's fine motor development is to stimulate the child's small muscles such as fingers and stimulate eye and hand coordination.Keywords: Learning art painting, finger painting technique and increasing fine motor developmentÂ